Differences in medical services in Nordic general practice: a comparative survey from the QUALICOPC study - Torunn Bjerve Eide; Jørund Straand; Cecilia Björkelund; Elise Kosunen; Ofeigur Thorgeirsson; Peter Vedsted; Elin Olaug Rosvold (Taylor & Francis Group, 2017)
Objective: We aim to describe medical services provided by Nordic general practitioners (GPs), and to explore possible differences between the countries. Design and setting: We did a comparative analysis of selected data from the Nordic part of the study Quality and Costs of Primary Care in Europe (QUALICOPC). Subjects: A total of 875 Nordic GPs (198 Norwegian, 80 Icelandic, 97 Swedish, 212 Danish and 288 Finnish) answered identical questionnaires regarding their practices. Main outcome measures: The GPs indicated which equipment they used in practice, which procedures that were carried out, and to what extent they were involved in treatment/follow-up of a selection of diagnoses. Results: The Danish GPs performed minor surgical procedures significantly less frequent than GPs in all other countries, although they inserted IUDs significantly more often than GPs in Iceland, Sweden and Finland. Finnish GPs performed a majority of the medical procedures more frequently than GPs in the other countries. The GPs in Iceland reported involvement in a more narrow selection of conditions than the GPs in the other countries. The Finnish GPs had more advanced technical equipment than GPs in all other Nordic countries. Conclusions: GPs in all Nordic countries are well equipped and offer a wide range of medical services, yet with a substantial variation between countries. There was no clear pattern of GPs in one country doing consistently more procedures, having consistently more equipment and treating a larger diversity of medical conditions than GPs in the other countries. However, structural factors seemed to affect the services offered.